Maternal Immune Activation in Mice Only Partially Recapitulates the Autism Spectrum Disorders Symptomatology. (1st October 2020) - Vigli, Daniele; Palombelli, Gianmauro; Fanelli, Sergio; Calamandrei, Gemma; Canese, Rossella; Mosca, Luciana; Scattoni, Maria Luisa; Ricceri, Laura
Highlights: Prenatal exposure to Poly I:C induces alterations in motor responses and in sensory gating, not in social responsiveness. Prenatal exposure to Poly I:C induces behavioural alterations that are comparable in male and female offspring. Brain levels of selected aminoacids are more variable in Poly I:C male than in vehicle male offspring. Abstract: Prenatal viral/bacterial infections are considered risk factors for autism spectrum disorders (ASD) and rodent models of maternal immune activation (MIA) have been developed and extensively used in preclinical studies. Poly inosinic-cytidylic acid (Poly I:C) was injected in C57BL6/J dams to mimic a viral infection on gestational day 12.5; the experimental design includes 10/12 litters in each treatment group and data were analysed always considering the litter-effect; neonatal (spontaneous motor behaviour and ultrasonic vocalizations) and adult [open field, marble burying, social approach, fear conditioning, prepulse inhibition (PPI)] offspring of both sexes were tested. In vivo magnetic resonance imaging/spectroscopy (MRI-MRS) and high-performance liquid chromatography (HPLC) to quantify both aminoacid and/or neurotransmitter concentration in cortical and striatal regions were also carried out. In both sexes high levels of repetitive motor responses and sensory gating deficits in PPI were the more striking effects of Poly I:C, whereas no alteration of social responses were evidenced. Poly I:C treatment did not affect mean values, but, intriguingly, increased variability in the levels of four aminoacids (aspartate glycine and GABA) selectively in males. As a whole prenatal Poly I:C induced relevant long-term alterations in explorative-stereotyped motor responses and in sensory gating, sparing cognitive and social competences. When systematically assessing differences between male and female siblings within each litter, no significant sex differences were evident except for increased variability of four aminoacid levels in male brains. As a whole, prenatal Poly I:C paradigms appear to be a useful tool to investigate the profound and translationally-relevant effects of developmental immune activation on brain and behavioural development, not necessarily recapitulating the full ASD symptomatology.